2020
DOI: 10.1177/1066896920918289
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Renal Neoplasm With Reverse Polarity: A Clinicopathologic Study of 7 Cases

Abstract: Papillary renal neoplasm with reverse polarity is a form of recently described tumor. These tumors are defined by GATA3 positivity, negative vimentin staining, and the presence of both papillary structures and a layer of eosinophilic cells with apical nuclei and a granular cytoplasm. In the present report, we review 7 cases of papillary renal neoplasm with reverse polarity that were GATA3+ and vimentin−, consistent with past reports. In all 7 of these cases, we found that these tumors were additionally positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 23 publications
(21 reference statements)
7
34
1
Order By: Relevance
“…In agreement with previous studies, 8–12 the 10 PRNRPs identified in our cohort presented with small tumour size, low pT stage, low WHO/ISUP nuclear grade and a very indolent clinical outcome. There was no recurrence or metastasis noted after complete surgical excision.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with previous studies, 8–12 the 10 PRNRPs identified in our cohort presented with small tumour size, low pT stage, low WHO/ISUP nuclear grade and a very indolent clinical outcome. There was no recurrence or metastasis noted after complete surgical excision.…”
Section: Discussionsupporting
confidence: 93%
“…Although Kim et al . reported four cases with WHO/ISUP grade 3 nuclei, 10 our results and other studies only found low‐grade nuclei in PRNRP 8,9,11,12 . Based on these findings, we propose the following histopathological criteria for the diagnosis of PRNRP: (1) predominant thin papillary or tubulopapillary growth, (2) focal or diffuse stromal hyalinisation, (3) eosinophilic, finely granular cytoplasm and (4) low‐grade (WHO/ISUP grades 1–2) apical nuclei.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations